Relationship between education level and understanding of fall risk increasing drugs in elderly - Febriyanti, Alifia Putri; Inayatilah, Fidia Rizkiyah; Dirgantara, Aprillia Angely Putri (International Journal on Health and Medical Sciences, 2023)
Increasing of life expectancy in Indonesia has an impact on increasing the number of elderly in Indonesia. Elderly is closely related to health problems. Falling is a major health problem that occurs in the elderly. Falling can reduce the quality of life of the elderly. Preventive action that can be taken to prevent falls in the elderly is to evaluate the understanding of the elderly regarding fall interventions. Fall risk increasing drugs is one of the fall interventions in the elderly. So that an evaluation of the understanding of elderly patients regarding fall risk increasing drugs can be carried out as a preventive action. The understanding of the elderly can be influenced by their last level of education. The elderly who live today received education in the past with all the limitations so that the participation of the elderly in the education sector is relatively low. The purpose of this research was to determine the relationship between knowledge level and elderly patients’ understanding of fall-risk increasing drugs. This research is a type of correlation analysis with a cross-sectional approach and uses a research instrument in the form of a closed questionnaire with a Guttman scale. The number of respondents in the research were 50 elderly patients who consume fall risk increasing drugs in the Health Center of Cukir, Jombang Regency. The research results showed that there were 38 respondents (86%) with basic education level, 6 respondents (12%) with intermediate education level, and 1 respondent (2%) with high education level. Respondents with less understanding were 19 respondents (38%), respondents with a sufficient level of understanding were 25 respondents (50%), and respondents with a high level of understanding were 6 respondents (12%). Based on the research conducted, it shows that there is a relationship between education level and understanding of elderly patients regarding falling risk drugs at the Cukir Health Center, Jombang Regency with a significance value of 0.001 with a unidirectional relationship and it is known that the strength of the relationship is moderate with a correlation coefficient value of 0.442